Genome sequence of Haemophilus parasuis strain 29755. Issue 1 (July 2011) - Mullins, Michael; Register, Karen; Bayles, Darrell; Dyer, David; Kuehn, Joanna; Phillips, Gregory
Abstract Haemophilus parasuis is a member of the familyPasteurellaceae and is the etiologic agent of Glässer's disease in pigs, a systemic syndrome associated with only a subset of isolates. The genetic basis for virulence and systemic spread of particularH. parasuis isolates is currently unknown. Strain 29755 is an invasive isolate that has long been used in the study of Glässer's disease. Accordingly, the genome sequence of strain 29755 is of considerable importance to investigators endeavoring to understand the molecular pathogenesis ofH. parasuis . Here we describe the features of the 2, 224, 137 bp draft genome sequence of strain 29755 generated from 454-FLX pyrosequencing. These data comprise the first publicly available genome sequence for this bacterium.